Evidence for the requirement of CydX in function but not assembly of the cytochrome bd oxidase in Shewanella oneidensis - Chen, Haijiang; Luo, Qixia; Yin, Jianhua; Gao, Tong; Gao, Haichun (Biochimica et biophysica acta, 2015)
Cytochrome bd oxidase, existing widely in bacteria, produces a proton motive force by the vectorial charge transfer of protons and more importantly, endows bacteria with a number of vitally important physiological functions, such as enhancing tolerance to various stresses. Although extensively studied as a CydA-CydB two-subunit complex for decades, the complex in certain groups of bacteria is recently found to in fact consist of an additional subunit, which is functionally essential. We investigated the assembly of the CydA-CydB complex using BiFC. We investigated the function of CydX using mutational analysis. CydX, a 38-amino-acid inner-membrane protein, is associated with the CydA-CydB complex in Shewanella oneidensis, a facultative anaerobe renowned for its respiratory versatility. It is clear that CydX is neither required for the in vivo assembly of the CydA-CydB complex nor relies on the complex for its translocation and integration into the membrane. The N-terminal segment (1-25 amino acid residues) and short periplasmic overhang of CydX, with respect to functionality, are important whereas the remaining C-terminal segment is rather flexible. Based on these findings, we postulate that CydX may function by positioning and stabilizing the prosthetic hemes, especially heme d in the CydA-CydB complex although a role of participating in catalytic reaction is not excluded. The work provides novel insights into our understanding of the small subunit of the cytochrome bd oxidase.